Novel metric for evaluating pre-exposure prophylaxis programme effectiveness in real-world settings - Hendrickson, Cheryl (Lancet HIV, 2020)
Although large-scale provision of HIV pre-exposure prophylaxis (PrEP) is gaining momentum, no systematic method to evaluate or compare the effectiveness of different scale-up strategies in real-world settings exists. To date, estimating the effectiveness of PrEP has relied on clinical trials or mathematical models. We propose a novel and pragmatic metric to evaluate and compare programme effectiveness using routine implementation data. Using South African and Zambian PrEP guidelines, we provide two examples of how to consistently measure PrEP-programme effectiveness with routinely collected data. PrEP effectiveness should account for HIV seroconversion, the variable risk of HIV infection (seasons of risk) estimated with routine risk assessment at each clinic visit (when available), and the persistence of PrEP use. Three criteria should be met in order to be considered a successful outcome: first, a person who initiates PrEP must not seroconvert; second, there should be no more than one period at high risk of HIV infection during the follow-up period when not taking PrEP; and finally, an individual must continue to attend health-care visits or discontinue prophylaxis in consultation with a health-care provider within a specified follow-up period. The number of PrEP successes could then be compared with the total number of people initiating PrEP to establish a success ratio. This outcome is a useful and easily interpretable metric to monitor effectiveness of PrEP programmes with routinely collected clinical data and can be used in cost-effectiveness analyses. These measurements allow for comparisons of scale-up strategies for PrEP programmes and, if widely adopted, will allow comparative studies of different approaches for PrEP service delivery.